2021
DOI: 10.24320/redie.2021.23.02.2945
|View full text |Cite
|
Sign up to set email alerts
|

Teaching to Self-Regulate in Mathematics: A Quasi-Experimental Study with Low-Achieving Elementary School Students

Abstract: Teaching students to self-regulate enhances their mathematics performance, yet few studies have investigated the long-term differential impact of particular self-regulation strategies specifically for low-achieving students. This quasi-experimental study evaluates the effect of teaching different self-regulation strategies on mathematical problem solving in low-achieving students. The participants were 69 sixth-grade elementary school students randomly assigned to one of three experimental groups (and taught p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Nevertheless, some other studies showed that ICT-based or -assisted mathematics learning did not have significant effect on students' numerical literacy [39][40][41][42][43][44][45][46][47][48][49]. Moreover, several studies found that ICTbased or -assisted mathematics learning had significant negative effect on students' numerical literacy [50][51][52][53][54][55][56][57][58][59][60]. Of these reports, it can be stated that ICT-based or -assisted mathematics learning has an inconsistent effect on the enhancement of students' numerical literacy skills, whereas clear and precise information regarding the consistency of the effectiveness of ICT use in mathematics learning for numerical literacy is required.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some other studies showed that ICT-based or -assisted mathematics learning did not have significant effect on students' numerical literacy [39][40][41][42][43][44][45][46][47][48][49]. Moreover, several studies found that ICTbased or -assisted mathematics learning had significant negative effect on students' numerical literacy [50][51][52][53][54][55][56][57][58][59][60]. Of these reports, it can be stated that ICT-based or -assisted mathematics learning has an inconsistent effect on the enhancement of students' numerical literacy skills, whereas clear and precise information regarding the consistency of the effectiveness of ICT use in mathematics learning for numerical literacy is required.…”
Section: Introductionmentioning
confidence: 99%